Features of Ukrainian Cartoons as Means of Charity Installation Formation (on the Example of Animated Series «Kotyhoroshko») - Туренко, Р.Л. (My University, 2016)
In the article the peculiarities of Ukrainian cartoons as a means of installation on charity (on the example of the animated series “Kotyhoroshko”)were defined. It was shown that the subjects have ambivalent attitude to charity. It was also found out the positive growth of settings on charity, which is reflected in the significant increase as compared to the factor of “Force” and “activity” concept of philanthropy and focus on altruism as the result of watching the cartoon, which can be explained by the viewer’s identification himself with positive characters of the animated series “Kotyhoroshko” and psychological action of the cartoon .
Keywords: Research Subject Categories::SOCIAL SCIENCES::Social sciences::Psychology; installation on charity, Ukrainian cartoons “Kotyhoroshko”, altruism.